2014
DOI: 10.1111/jsm.12297
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Outcomes and Patients' Satisfaction with Suprapubic Phalloplasty

Abstract: Introduction Many techniques, specifically forearm free flap phalloplasty, are used in penile reconstructive surgery. Although satisfying, a major disadvantage is the large, stigmatizing scar on the donor site, which leads many patients to explore alternatives. Aim The aim of this study is to assess the outcomes and satisfaction of patients offered the choice between metaidioplasty, forearm free flap, and suprapubic phallopla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
39
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 70 publications
(41 citation statements)
references
References 44 publications
1
39
0
1
Order By: Relevance
“…Timsit et al [21] reported 6 radial forearm free-flap phalloplasty operastions due to bladder exstrophy and unsatisfactory penile appearance and there were 3 complications in the postoperative period. Terrier et al [1] reported the results of 24 patients and 23 of them were due to female-to-male gender reassignment,1 of them was due to penile amputation. Neophallus survived in all patients and overall satisfaction was 95%.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Timsit et al [21] reported 6 radial forearm free-flap phalloplasty operastions due to bladder exstrophy and unsatisfactory penile appearance and there were 3 complications in the postoperative period. Terrier et al [1] reported the results of 24 patients and 23 of them were due to female-to-male gender reassignment,1 of them was due to penile amputation. Neophallus survived in all patients and overall satisfaction was 95%.…”
Section: Resultsmentioning
confidence: 99%
“…Terrier et al [1] 24 23 Female-to-male transgender 1 Penil amputation Suprapubic phalloplasty (3 stages)…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations